Monitoring the impact of COVID-19 in Myanmar: Rice millers - July 2020 survey round - Goeb, Joseph; Tang, Yulu; Zone, Phoo Pye (International Food Policy Research Institute, 2020)
To understand how Myanmar’s rice value chain has been affected by the COVID-19 crisis, a series of phone interviews are being conducted with rice millers from Ayeyarwady, Bago, and Yangon. This report presents results from the first round of interviews that was conducted in July 2020 with 404 medium- and large-scale mill owners and managers. Key Findings Strikingly, 60 percent of mills are anticipating a revenue drop of at least 30 percent this year compared to 2019. Only 3 percent of mills are expecting an increase in revenue. Just over half of the mills interviewed experienced disruptions in selling milled rice and in buying paddy. However, those impacts have lessened considerably, as only 15 percent of millers reported experiencing those disruptions in the past 30 days. Almost all mills regarded byproduct sales as important to their business. Roughly half reported no changes in byproduct prices compared to 2019, but one-quarter reported price increases, while the other quarter reported decreases. Mills from Ayeyarwady have been more negatively impacted by lower byproduct prices than elsewhere. For most mills, both paddy purchase and rice sales prices are now slightly higher than the 2019 average. Interestingly, prices increased more for low-quality varieties than for high-quality varieties. Margins for low-quality varieties have increased relative to 2019, while they have decreased for high-quality varieties. Thus, mills producing larger quantities of high-quality rice now may be adversely affected by lower margins. Recommended Actions Continue and expand the government relief loan program offered to small and medium enterprises – Action 2.1.1 under the COVID-19 Economic Relief Plan (CERP) of the Government of Myanmar. This would assist mills struggling with lower revenues and buffer smaller mills from further shocks during the crisis. Government should extend tax relief to mills hard hit by the COVID-19 crisis through waivers or deferrals (CERP Action 2.1.3). Government should facilitate exports by putting in place easier licensing processes (CERP Action 2.4.3), such as allowing licenses to be obtained online.